The Role of Artificial Intelligence in Criminal Investigations in India - Kumar, Navin (Journal of Legal Studies, 2025)
With an increasing presence, Artificial Intelligence in Criminal Investigations all over the globe is progressively emerging as a new tool. Applications of Artificial Intelligence in India have been rapidly proliferating, especially as criminal activities increasingly move into the online sector. The volume of evidence collected is experiencing exponential growth and traditional methods often lack the power and complexity required to address modern crime effectively. India's law enforcement agencies are seeking to embrace these through AI technologies and enhance their powers in solving crimes more effectively and efficiently. All these technologies like; predictive policing, facial recognition, natural language processing, or data analytics represent a pathway to faster speeds, higher accuracies, and better outcomes in Criminal Investigations. Predictive policing algorithms can be used to predict crime hotspots, while facial recognition systems can help identify suspects in a matter of minutes rather than hours and days taken in the manual methods. Moreover, AI can help in curbing cybercrime, which is the most challenging for law enforcement agencies in India at present. However, this use of AI in Criminal Investigation also raises concerns, particularly in the space of privacy and surveillance, protection of data and algorithmic bias. More specifically, the country’s regulatory framework for the use of AI by law enforcement agencies is extremely weak and underdeveloped, which opens the door to abuse and the infringement of certain fundamental rights. This paper examines the advantages as well as disadvantages of Artificial Intelligence in relation to Criminal Investigations in India and lays out a lengthy list of issues that must be resolved before AI can be applied to the nation's criminal matters.